EVALUASI PENGEMBANGAN KAPASITAS MASYARAKAT SEBAGAI DESA TANGGUH BENCANA DI DESA LEBIH, GIANYAR, BALI - I Putu Wahyu Wedanta Pucangan; Wahyudi Arimbawa (Pranatacara Bhumandala: Jurnal Riset Planologi, 2020)
Lebih Village is located in the southernmost part of Gianyar Regency, directly adjacent to the Indian Ocean so that the potential for abrasion or tsunami is high. One of the strategies that will be used to realize is by increasing the capacity of community adaptation in disaster risk reduction through the development of villages that are resilient to disasters triggered by the National Disaster Management Agency (BNPB). The purpose of this study is to determine the level of resilience to the tsunami and abrasion and the success rate of community adaptation capacity to disaster risk reduction in Desa Lebih in the Disaster Resilient Village program. This study uses a descriptive research method with a qualitative approach and support for quantitative data obtained through parameters from each aspect of the Disaster Resilient Village, interviews, and complete observation. Data will be analyzed by scoring the analysis method. Based on the data analysis conducted, it was concluded that from the results of the accumulation of scoring the level of resilience to the tsunami and abrasion disaster in Desa Lebih more to 2.6 which means it is in the category of "Medium Disaster Resilient Village", and the success rate of community adaptation capacity to disaster risk reduction in Desa Lebih reached 2.9 which means it is in the category of "Successful".